IMPROVING THE CYBERSECURITY SYSTEM OF BANK PLASTIC CARDS - Kurbonbekova Mohichehra Turobjonovna,; Maxmudova Muxlisa Qodirjon qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
This article theoretically argues that digital transformation is a strategic necessity for banks to remain competitive with fintech companies as a result of rapid technological advancements in digital transformation. In addition, the theoretical foundations of digital transformation in retail banking are critically examined, and the main principles of diffusion of innovation theory, resource-based view (RBV), institutional theory, service-oriented logic (SDL), technology adoption models, and dynamic capabilities are extensively analyzed. It is argued that digital transformation is not just about implementing digital tools, but also about creating value, delivering services, working with customers, improving efficiency, and increasing interbank competitiveness. By analyzing a large body of scientific literature, the study identifies gaps in existing theoretical frameworks and attempts to identify how banks can adapt to the digital economy, increase investment in innovation, and become digitally mature. Such analyses contribute to the field both scientifically and practically by offering comprehensive development models to understand the systemic and multidimensional dynamics of digital transformation in retail banking.